PENGEMBANGAN BUTIR SOAL HIGHER ORDER THINKING SKILL (HOTS) MATERI SISTEM KOORDINASI PADA SISWA SMA KELAS XI - Mustofa, Ali (JPB - Jurnal Pendidikan Biologi, 2021)
Conducting an assessment is one of the teacher's duties apart from compiling a learning program and implementing it in the classroom. The teacher must also be able to determine what can be obtained or achieved from the learning process that has been organized. The purpose of this study was to develop HOTS questions on the coordination system material and to test the quality of HOTS questions in the coordination system material for high school students in grade X. The subjects of this study consisted of 18 students who were selected purposively. Analysis of the items consisted of validity, reliability, difficulty level, differentiation, and trick effectiveness. The results of the analysis of the validity of the questions with a significant level of 5% for 18 students obtained 50 questions (92%) valid. The results of the reliability test of the items obtained the reliability index in the "high" criteria. So the items have high consistency in measuring the ability of students regarding the material of the coordination system to distinguish high-skilled students from low-ability students. The results of the analysis of the difficulty level of the questions were: 26 questions (5%) had an easy difficulty level, 9 questions (75%) had a moderate difficulty level and 15 questions (20%) had a difficult difficulty level. Overall, there were 4 distractor test results that did not function. A bully is said not to function if less than 5% of all test takers are selected. The crooks that didn't work need to be revised again. The results of the 84% difference power test were rejected so it needed to be revised.